Fontes de ácidos graxos insaturados na alimentação de vacas leiteiras no período seco - Bettero, Vitor Pereira [UNESP] (2015)
The objective of this study was to evaluate the effects of sources of unsaturated fatty acids to dairy cows in the dry period on the ruminal dynamic and biohydrogenation and intestinal flow of fatty acids. Eight Holstein dry cows cannulated in the rumen and abomasum (614 ± 59 kg of body weight; mean ± SD), were assigned randomly in two contemporary and balanced 4 x 4 Latin squares, fed the following diets: 1) control (C) diet based on corn and soybean meal; 2) refined soybean oil (SO) with addition of 3.0% on total DM 3) Whole soybean raw (WS), with the inclusion of 16.0% on total DM; and 4) calcium salts of unsaturated fatty acids (CS), with the inclusion of 3.2% on total DM. The DM, OM, CP, NDF and TDN intakes did not differ (P> 0.05) between treatments. Diets with fat sources had higher intake of EE (0.72 vs 0.30 kg/day) and lower intake of NFC (3.91 vs 4.40 kg/day) when compared to control. The digestibilities of DM, OM and NDF were higher (P <0.05) in treatment C compared to treatments with lipid addition. In relation to EE, the digestibility of C diet was lower than in other treatments (84.88% vs 86.93%). The concentration of NH3-N was higher (P <0.05) in animals fed C diet than the diets with lipids inclusion (20.39 vs. 17.49 mg/dL). The C diet had the lowest propionate concentration in relation to lipid sources. The SO diet had higher propionate concentrations (P <0.05) compared to WS and CS diets. The acetate: propionate ratio (C2/C3) was higher (P <0.05) in the control diet (4.13) than the diets with supplementation (3.81). The microbial protein synthesis and energy and nitrogen balances were not affected by diets. Animals fed diets with fat supplements had higher total cholesterol and HDL cholesterol in the blood (P <0.05). The SO diet had lower ruminal digestion rates (P <0.05) for DM, NDF and pdNDF compared to WS and CS. WS diet had lower passage rates of DM, NDF and pdNDF (P <0.05) in relation to CS diet ...